Literature Review : Risk Factors Wood Dust Exposure on Workers Lung Status - Faradilla Nikmah (Universitas Airlangga, 2020)
Introduction: Health problems caused by environmental factors are still one of the main things to note. One of the dangers in the work environment is the presence of organic dust including wood dust. Organic dust flying in the air is able to interfere with the health of the workers through the respiratory tract. The resulting wood dust is at risk causing lung faal status disorders in workers. This article aims to explore risks factors for wood dust exposure to the status of lung faal in wood industry workers based on the previously performed research from published journals. Discussion: This research used a method of literature study with a comparative study approach. The selected research should be in appropriated with the topic and through the protocols that have been set to become secondary data. The results of data analysis indicated that almost all research use observational analytic types with cross sectional approaches. Wood dust that has entered through the respiratory tract worker is influenced by several variables. The most often used risk factors as a research variable are dust levels, age, use of PPE, and smoking habit. Conclusion: The research can be concluded that independent variables of selected research are less varied. The selected research variables already existed in previous research. Upcoming researchers are expected to be able display new variables that are suspected to affect the status of the lung Faal on wood industry workers.